Pengembangan E-Modul Interaktif Berbasis Flipbook pada Materi Sistem Informasi dan Komunikasi Organisasi di SMKN 40 Jakarta - Eka Putri Yulfani; Roni Faslah; Maulana Amirul Adha (Politeknik Kampar, 2025)
This study aims to develop an interactive e-module based on Flipbook for the Organizational Information and Communication Systems Phase E in Grade X Office Management at SMKN 40 Jakarta and to evaluate its acceptability based on assessments from subject matter experts, media experts, and student trials. The background of this research is the insufficient availability of textbooks for students and the importance of utilizing technology to support the teaching and learning process. The research method used is Research and Development (R&D) with the ADDIE development model, which consists of the following stages: Analysis, Design, Development, Implementation, and Evaluation. The validation results from subject matter experts indicate that the developed interactive e-module received a score of 96%, which falls into the